Investigating genome variation within a South African wild dog (Lycaon pictus) population: Towards understanding their susceptibility to Mycobacterium bovis infection - Meiring, Christina (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.